Echocardiography to estimate high filling pressure in patients with heart failure and reduced ejection fraction. (21st July 2020) - Romano, Giuseppe; Magro, Serena; Agnese, Valentina; Mina, Chiara; Di Gesaro, Gabriele; Falletta, Calogero; Pasta, Salvatore; Raffa, Giuseppe; Baravoglia, Cesar Mario Hernandez; Novo, Giuseppina; Gandolfo, Caterina; Clemenza, Francesco; et al.
Abstract: Aims: Echocardiographic assessment of left ventricular filling pressures is performed using a multi‐parametric algorithm. Unselected sample of patients with heart failure with reduced ejection fraction (HFrEF) patients may demonstrate an indeterminate status of diastolic indices making interpretation challenging. We sought to test improvement in the diagnostic accuracy of standard and strain echocardiography of the left ventricle and left atrium (LA) to estimate a pulmonary capillary wedge pressure (PCWP) > 15 mmHg in patients with HFrEF. Methods and results: Out of 82 consecutive patients, 78 patients were included in the final analysis and right heat catheterization, and echocardiogram was performed simultaneously. According to the univariable analysis, E wave velocity, the ratio between E‐wave/A‐wave (E/A, area under the curve [AUC] = 0.81, respectively), isovolumic relaxation time (AUC = 0.83), pulmonary vein D wave (AUC = 0.84), pulmonary vein S/D Ratio (AUC = 0.85), early pulmonary regurgitation velocity (AUC = 0.80), and accelerationa time at right ventricular out‐flow tract (RVOT AT, AUC = 0.84) identified with the highest accuracy PCWP > 15 mmHg. They were all tested in multivariate analysis, and they were not independently correlated with PCWP. Tricuspid regurgitation (TR) velocity was measurement with the highest predictive value in identifying PCWP > 15 mmHg (AUC = 0.89), compared with other established parameters such as the ratio between e‐wave velocity divided by mitral annular e' velocity (E/e'), deceleration time, or LA indexed volume (LAVi), which all reached a lower accuracy level (AUC = 0.75; 0.78; 0.76). Among strain measures, global longitudinal strain in four chamber view (GLS 4ch), the ratio between e‐wave velocity divided by mitral annular e' strain rate (E/e'sr), and LA longitudinal strain at the reservoir phase were helpful in estimating elevated PCWP (AUC = 0.77; 0.76; 0.75). According to multivariable analysis, the following two models had the greatest accuracy in detecting PCWP > 15 mmHg: (i) TR velocity, LAVi, and E wave velocity (receiver operating characteristic [ROC]‐AUC = 0.98), (ii) AT RVOT, LAVi and GLS 4ch (ROC‐AUC = 0.96). Neither E/A (ROC‐AUC = 0.81) nor E/e' (ROC‐AUC = 0.75) was an independent predictor when included in the model. The two MODELS were applicable to the entire population and demonstrated better agreement with the invasive reference (91% and 88%) than the guidelines algorithm (77%) regardless of the type of rhythm. Conclusions: Our suggested echocardiographic approach could be used to potentially reduce the frequency of "doubtful" classification and increase the accuracy in predicting elevated left ventricular filling pressure leading to a decrease in the number of invasive assessment made by right heart catheterization.